Large vertical hysteretic shift and signature of exchange bias in BiFeO3/SrRuO3 heterostructure. Issue 16 (November 2019) - Singh, Anar; Chen, Jingsheng
Abstract: We present the results of magnetic study on G-type antiferromagnetic BiFeO3 /ferromagnetic SrRuO3 heterostructure grown on (001) SrTiO3 substrate using pulsed laser deposition technique. We observe a large positive vertical magnetization shift (MShift 35%) in the magnetic hysteresis (M − H) loop in the direction of the cooling fields (±30 kOe). The MShift is essentially due to the presence of the interfacial pinned Ru 4+ moments and the local defects/vacancies present in the SRO layer. The pinned Ru 4+ moments strongly attached to Fe 3+ moments of BiFeO3 layer through exchange interaction may result in the exchange bias (EB) effect. The positive MShift and negative EB effect suggest the ferromagnetic double exchange interaction Fe 3+ -O-Ru 4+, across the interface.